2022
DOI: 10.3390/su14031589
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability and Employability in the Time of COVID-19. Youth, Education and Entrepreneurship in EU Countries

Abstract: This paper aims to identify several changes in the labor market structure in COVID-19 pandemic times. The context of the research is represented by the influence of the COVID-19 pandemic in the economic field, especially at the labor market level. This difficult situation could generate a negative impact in the sphere of traditional jobs and economic sectors. The main challenge for sustainable development in this new global situation is represented by human sustainability. Related to human sustainability, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 68 publications
1
13
0
Order By: Relevance
“…With the increased flow of migrants generated by the ongoing war in Eastern Europe, coupled with the impact of the negative economic factors that are currently manifesting themselves, there is a possibility that a number of indicators will be negatively influenced, leading to a decrease in the rate of progress towards the SDG 10 targets. Similar conclusions, supporting our findings, have also been published by Gavrilut , ă et al [64], Bieszk-Stolorz and Dmytrów [65], or Kolluru and Semenenko [66].…”
Section: Resultssupporting
confidence: 94%
“…With the increased flow of migrants generated by the ongoing war in Eastern Europe, coupled with the impact of the negative economic factors that are currently manifesting themselves, there is a possibility that a number of indicators will be negatively influenced, leading to a decrease in the rate of progress towards the SDG 10 targets. Similar conclusions, supporting our findings, have also been published by Gavrilut , ă et al [64], Bieszk-Stolorz and Dmytrów [65], or Kolluru and Semenenko [66].…”
Section: Resultssupporting
confidence: 94%
“…Involvement in sustainable development can reduce future shocks in economic and social systems (Gavriluţȃ et al, 2022). This issue was further elaborated on by the same expert.…”
Section: Sustainabilitymentioning
confidence: 99%
“…Several studies showed a correlation between SARS-CoV-2 levels in wastewater and positive COVID-19 cases reported from clinic testing or public records, suggesting that wastewater-based monitoring can provide information for large-scale dynamic of the pandemic [ 5 , 6 , 7 , 8 , 9 ]. Although it is important to investigate the COVID-19 prevalence and dynamic in communities and cities scales, with the negative economic impact of the COVID-19 around the world, the interests of business owners lay in the presence of the viruses and infected individuals in the local facility, which is crucial for updating the control procedures in a timely manner to respond to the decreasing or rising risks and ensuring the safety of the workers during the business recovery stage [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%